(untitled) (Scientific journal of the Fergana State University, 2025)
This article is devoted to studying the possibilities of forming and developing professional skills through simulation technologies in teaching English to students of the pediatrics department at the Fergana Medical Institute of Public Health. As part of the study, the results of students who received training using simulation methods and students who studied in the traditional way were analyzed. The results of the experimental study showed that students trained through simulations achieved high results in terms of diagnostics, communication in medical English, and stress tolerance. The article also considers the problems in the implementation of simulation technologies and ways to overcome them. Based on the results of the study, it was proven that simulation approaches are effective in medical education, and practical recommendations were developed for the widespread introduction of this method in pediatrics.